Evolution from small molecule to nano-drug delivery systems: An emerging approach for cancer therapy of ursolic acid - Jingwei Shao; Yifan Fang; Ruirui Zhao; Fangmin Chen; Mingyue Yang; Jiali Jiang; Zixuan Chen; Xiaotian Yuan; Lee Jia (Elsevier, 2020)
Ursolic acid (UA), a natural pentacyclic triterpenoid, possesses widespread biological and pharmacological activities. However, drawbacks such as low bioavailability, poor targeting and rapid metabolism greatly hinder its further clinical application. Recently, with the development of nanotechnology, various UA nanosystems have emerged as promising strategies for effective cancer therapy. This article reviews various types of UA-based nano-delivery systems, primarily with emphasis placed on novel UA-based carrier-free nano-drugs, which are considered to be innovative methods for cancer therapy. Moreover, this review presents carrier-free nano-drugs that co-assembled of UA and photosensitizers that displayed synergistic antitumor performance. Finally, the article also describes the development and challenges of UA nanosystems for future research in this field. Overall, the information presented in this review will provide new insight into the rational utilization of nano-drugs in cancer therapy.